The role of vacuum circuit breakers in traction substations - Juraeva Kamila Komilovna; Rustemova Aynura Rustemovna (International Journal on Orange Technologies, 2020)
The railway power supply system is the main hardware circuit breaker between the electrical equipment and devices used in traction substations, and the continuity and reliability of the power supply is directly related to it.